2016
DOI: 10.1111/1744-7917.12368
|View full text |Cite
|
Sign up to set email alerts
|

The chemosensory appendage proteome of Amblyomma americanum (Acari: Ixodidae) reveals putative odorant‐binding and other chemoreception‐related proteins

Abstract: Proteomic analyses were done on 2 chemosensory appendages of the lone star tick, Amblyomma americanum. Proteins in the fore tarsi, which contain the olfactory Haller's organ, and in the palps, that include gustatory sensilla, were compared with proteins in the third tarsi. Also, male and female ticks were compared. Proteins were identified by sequence similarity to known proteins, and by 3-dimensional homology modeling. Proteomic data were also compared with organ-specific transcriptomes from the tick Rhipicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 52 publications
(66 reference statements)
6
78
0
Order By: Relevance
“…The other two Varroa OBPs lacked the conserved domain, but significantly matched 'OBP-like' sequences identified in I. scapularis, G. occidentalis and A. americanum and reported by Renthal et al, (2017) (BLASTn, e-value < 1E-20). Four of the six Varroa OBPs were identified according to the presence of the insect OBP conserved domain (IPR036728).…”
Section: Two Families Of Soluble Carrier Proteins: Npc2 and Obpssupporting
confidence: 64%
See 4 more Smart Citations
“…The other two Varroa OBPs lacked the conserved domain, but significantly matched 'OBP-like' sequences identified in I. scapularis, G. occidentalis and A. americanum and reported by Renthal et al, (2017) (BLASTn, e-value < 1E-20). Four of the six Varroa OBPs were identified according to the presence of the insect OBP conserved domain (IPR036728).…”
Section: Two Families Of Soluble Carrier Proteins: Npc2 and Obpssupporting
confidence: 64%
“…of the 'OBP-like' proteins reported by Renthal et al, (2017), and found four Varroa transcripts (local BLAST, e-value < E-20), two of which also classified as 'OBP' containing the insect-OBP domain in addition to a signal peptide in the N-terminal of the open reading frame (ORF). of the 'OBP-like' proteins reported by Renthal et al, (2017), and found four Varroa transcripts (local BLAST, e-value < E-20), two of which also classified as 'OBP' containing the insect-OBP domain in addition to a signal peptide in the N-terminal of the open reading frame (ORF).…”
Section: Annotation Of Chemosensory-related Transcripts and Proteinsmentioning
confidence: 99%
See 3 more Smart Citations